ENDOSCOPIC SURGERY FOR TREATING SPINAL STENOSIS: AN INTEGRATIVE REVIEW OF RANDOMIZED CLINICAL TRIALS - Rafael Augusto da Silva Aparício; Rodrigo Freitas Maringoni de Oliveira; Felipe de Almeida Pinto; Carlos Gorios; Lorran Azevedo Zanon; Alessandra Masi (Acta Ortopédica Brasileira)
ABSTRACT Background: Spinal stenosis refers to the narrowing of the spinal canal which can generate clinical symptoms secondary to the spinal cord injury itself, or even root involvement. The traditional open surgical procedure to correct spinal stenosis is highly traumatic and risky, and with the development of surgical techniques, endoscopic procedures have been widely used in treating said stenosis, achieving good results with minimally invasive management. Aim: To conduct a literature review regarding endoscopic techniques for correcting spinal stenosis. Method: This is an integrative literature review that surveyed the PUBMED database using the following search strategy: spinal[title] AND stenosis[title] AND surgery[title]. Only randomized clinical trials published in the last 10 years were included in the sample. Results: A total of 13 articles were identified that met the previously established search strategy, all of which were included in the review. Conclusion: The reviewed studies showed that endoscopic surgery to correct spinal stenosis could offer adequate decompression of neural elements, resulting in shorter hospital stays, faster recovery and favorable operative results. Level of Evidence IV, evidence from descriptive (non-experimental) or qualitative studies.